“Modul Elektronik Berbasis STEM: Kunci untuk Membuka Kreativitas Siswa di Era Digital” - Permata Sari, Devi; Wiyono, Ketang; Siahaan, Sardianto Markos (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2025)
This research is classified as qualitative descriptive research. This study aims to assess the need for the use of E-Modules as a tool in high school physics subjects. This research uses a qualitative descriptive approach. The research survey questionnaire as an instrument. The questionnaire was distributed through a google form link, which was then filled in online by 1st and 3rd semester students who had studied physics subjects especially the subject of alternating current electricity. This research focuses on high school students class XII. The research involved 54 student respondents. The results showed that all respondents or 100% of students stated that they really need STEM-based learning to be used as a learning resource. Based on this research, there is a need for a learning E-Module as a learning media. This preliminary research will be developed into further research to create a STEM-based learning E-Module to train creative thinking skills on direct current electricity material